Gamma exposure buildup factors and neutron total cross section of ceramic hosts for high level radioactive wastes. (April 2018) - Singh, V.P.; Badiger, N.M.; Korkut, Turgay
Abstract: Mass attenuation coefficients and exposure buildup factors (EBF) for some ceramic hosts such as Hollandite (BaAl2 Ti6 O16 ), Perovskite (CaTiO3 ), Zirconolite (CaZrTi2 O7 ), Apatite (Pb10 (VO4 )4.8 (PO4 )1.2 I2 ), and Zircon (ZrSiO4 ) for high level radioactive waste have been computed in the present paper. The mass attenuation coefficients for the Apatite were found to be the highest. The EBF for the Apatite were found the smallest in low-to-intermediate energy (<3 MeV). Neutron total macroscopic cross sections for the ceramic hosts were calculated for 2, 4.5 and 14.1 MeV using Geant4. Zircon for neutron low-energy (2 MeV) and Hollandite for high-energy (14.1 MeV) were found superior shielding materials. This study could be useful for radioactive waste management, handling, transportation, dose evaluation and other shielding requirements. Highlights: We calculated EBF for ceramic hosts for the HLW using G-P fitting method. We calculated neutron total macroscopic cross sections using Geant4. Apatite was found most suitable superior ceramic host for the HLW. Neutron shielding properties for Zircon at 2 MeV were found superior.